Reciprocity and Exploitation: Peasant Women in Malaysia's Industrialization Process - McLellan, Susan (My University, 1986)
The case of Malaysia as an industrializing country is contrary to the predictions of world systems theory. The ethnic imperatives of the state's New Economic Policy has necessitated the successful manipulation, and accumulation, of foreign and domestic capital for the economic development process. Although Malaysia enjoys an impressive rate of growth, the way in which the benefits are allocated by the state elite has resulted in the increased economic inequality of the labour force. The fact that development is taking place is partly the result of the 'exploitation' of the labour force which, in Malaysia's development process, remains rooted firmly in, and dependent upon, the non-valorised 'reciprocal' labour of kin. Exploitation and reciprocity are developed as a conceptual framework within which the field is analyzed. The dissertation examines the way in which reciprocity - a multidimensional phenomena - is utilised at different levels of Malaysia's development process. Reciprocal obligations link peasant households to the production processes of state and foreign capital. The study draws particular attention to the position of young Malay women who work in transnational corporations producing goods for international markets and in household subsistence production. The gender specific nature of Malaysia's industrial labour force dictates that it receives few benefits from state prosperity. The way in which the work force survives by 'occupational multiplicity' in the interstices of industrial wage labour, 'reciprocity' and subsistence production, forms the theoretical and empirical focus of the dissertation. Malaysia's new semiproletariat sustain themselves and their households in subsistence production by an amalgamation of intra and inter household reciprocity. In this way their non valorised labour contributes to the State's New Economic Policy.
Keywords: Anthropology; Anthropology